California Bowl Football Game at Bulldog Stadium; Eastern Michigan Hurons 30 v. San Jose Spartans 27 - Watkins, Howard::::::::: (1987)
Scoreboard with final score Eastern Michigan 30 and San Jose State 27 Fans exiting south end of Bulldog stadium at sunset